2021
DOI: 10.1159/000518457
|View full text |Cite
|
Sign up to set email alerts
|

How Yucatec Maya Children Learn to Help at Home

Abstract: Children’s household contributions have been studied across cultural communities, mostly on the basis of maternal reports. Less is known about children’s views of their contributions. This study examines Yucatec Maya children’s ethnotheories of learning to help at home and their motivation for helping. We interviewed 38 7- to 11-year-old children in two communities in the Yucatán Peninsula, México. Children in both communities contributed substantially to their families by regularly taking the initiative to he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 47 publications
1
14
0
1
Order By: Relevance
“…Similar to mothers' reports in this study, Yucatec Maya children also reported learning by observing others work and taking the initiative to help (Alcalá et al, 2021). For example, children mentioned that they learn to cook or take care of a younger child by observing others and getting involved.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Similar to mothers' reports in this study, Yucatec Maya children also reported learning by observing others work and taking the initiative to help (Alcalá et al, 2021). For example, children mentioned that they learn to cook or take care of a younger child by observing others and getting involved.…”
Section: Discussionsupporting
confidence: 85%
“…Our sample consisted of 23 mothers of children who participated in the study and were enrolled from the local elementary schools (Alcalá et al, 2021). There were 15 from Chan Cah and 8 from Nunkiní.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indigenous systems of relationality—the ethics, worldviews, beliefs and practices, and moral precepts of being in relation with the rest of the living world—are the cornerstone of Indigenous knowledges as well as Indigenous families and communities (Cajete, 2015). Through these systems of relationality, young people learn what it means to be a responsible family member and person in the world (Alcalá et al, 2021), the nature of relational responsibility, and how to participate in communal life through everyday social and cultural experiences (Cajete, 2015). Passed down from one generation to the next, relational frameworks are deeply embedded within Indigenous knowledge systems and support the health and well-being of Indigenous peoples (Elliott-Groves et al, 2020).…”
Section: Why Indigenous Systems Of Relationality?mentioning
confidence: 99%
“…While there are of course many aspects of children's and families' lives that differ across these settings, we focus on three domains of the Yucatec Maya cultural framework characterizing children's roles in family life (Gaskins, 2020). Gaskins (2020) has recently synthesized the ethnographic record on Yucatec Maya families to posit core domains that ordinarily organize Yucatec Maya children's lives: children's autonomy, belonging, and family work (also see Alcalá et al, 2014Alcalá et al, , 2018Alcalá et al, , 2021Coppens et al, 2016;Cervera, 2016;Gaskins, 1999Gaskins, , 2000Gaskins, , 2006Gaskins, , 2014b. While in fact these three domains are integrated into a unified childhood experience, they are helpful analytical tools to allow us to articulate cultural differences in the ground rules of family life.…”
mentioning
confidence: 99%